2019
DOI: 10.3389/fphar.2019.01471
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Species in Cordyceps sinensis and Its Potential Health Risks

Abstract: High arsenic residues make Cordyceps sinensis a concern in China. Arsenic toxicity is related to its species. Many studies have evaluated the toxicity of total arsenic, but few have studied its species. In this study, the species of arsenic in C. sinensis and its potential health risk were investigated. SEC-HPLC-ICP-MS was used to analysis of arsenic in C. sinensis and unknown arsenic (uAs) was discovered. Additionally, arsenic in C. sinensis was mainly found in alkali-soluble proteins. The trend of arsenic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…HNO 3 solution is superior for recovery of iAs compared to simulated gastrointestinal juice. The results of Guo et al [ 21 ], Zuo et al [ 22 ], Zhou et al [ 23 ], Li et al [ 24 ], and the present research all support this conclusion.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…HNO 3 solution is superior for recovery of iAs compared to simulated gastrointestinal juice. The results of Guo et al [ 21 ], Zuo et al [ 22 ], Zhou et al [ 23 ], Li et al [ 24 ], and the present research all support this conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies indicate that the unknown arsenic species were in organic form and Guo's results [ 22 ] supported this conclusion using an H 2 O 2 oxidation test. Li et al [ 24 ] showed that unknown organic arsenic was abundant in wild C. sinensis using SEC-HPLC- ICP- MS and continuous extraction methods. Arsenic is distributed in lipids, proteins, polysaccharides, and other chemical compositions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic (As) is a carcinogenic and highly toxic metalloid found diffusely in the earth's crust, water, soil, plants, and food. 1,2 As can accumulate in the human body through food intake, which is a serious health risk to consumers. Inorganic arsenic (Asi), mainly arsenite and arsenate, is listed as a Group I carcinogen by the International Agency for Research on Cancer (IARC) and presents potential damage to the skin, lungs, kidneys, nervous system, respiratory system, and urinary system.…”
Section: Introductionmentioning
confidence: 99%
“…Rice products, such as rice wine, are also affected. 1,6 The toxicity of As depends strongly on the compounds it forms with specific chemical structures, rather than merely the total content. Asi has proved to be more poisonous than the organic As species, including monomethylarsonic acid, dimethylasinic acid (DMA), arsenobetaine (AsB), arsenocholine (AsC), and arsenosugars.…”
Section: Introductionmentioning
confidence: 99%